Histological recovery and gluten‐free diet adherence: a prospective 1‐year follow‐up study of adult patients with coeliac disease. Issue 6 (28th July 2014) - Galli, G.; Esposito, G.; Lahner, E.; Pilozzi, E.; Corleto, V. D.; Di Giulio, E.; Aloe Spiriti, M. A.; Annibale, B.
Summary Background Adequate gluten‐free diet (GFD) is the only treatment for coeliac disease (CD). However, no agreement has been reached on either how and when to assess patient adherence to GFD or its effectiveness on villous atrophy. Aim To assess, in a prospective study, patient adherence to and efficacy of GFD on histological recovery after 1‐year of GFD. Methods Between 2009 and 2012, we enrolled 65 consecutive newly‐diagnosed adult patients (median age 38 years, 18–70) with biopsy‐proven atrophic CD. Patients were re‐evaluated after 1 year of GFD with duodenal histology, serological assays, symptoms and a dietary interview based on a validated questionnaire. Complete histological recovery was defined as the absence of villous atrophy and ≤30/100 intraepithelial lymphocytes. Results Overall, 81.5% of patients had adequate adherence (ADA) to GFD, whereas 18.5% had an inadequate adherence (IADA); 66% of ADA patients and no IADA patients achieved complete histological recovery (P < 0.00001). Among ADA patients, antibody seroconversion and symptoms were not significantly different between patients who achieved complete histological recovery and those who achieved partial histological recovery with P = 0.309 and P = 0.197, respectively. Multivariate analysis showed that Marsh 3C was a risk factor for incomplete histological recovery in ADA patients (OR 8.74, 95% CI: 1.87–40.83). Conclusions This study shows that complete histological recovery after 1‐year of GFD in adult patients, who are assessed as adherent to the GFD, can be obtained in 66% of patients. Patients with severe histological damage at diagnosis are at risk for incomplete histological recovery 1 year later.